Ketegangan Hukum Antara Sanksi Adat Kasepekang Dengan Humanisme Hukum Di Desa Adat Paselatan, Kabupaten Karangasem, Bali - I Putu Sastra Wibawa; Mahrus Ali (Jurnal Hukum IUS QUIA IUSTUM, 2022)
The arena of tension between kasepekang indigenous sanctions and legal humanism occurred in the Paselatan Traditional Village, Karangasem Regency, Bali. One family residing in the traditional village received customary sanctions in the form of being temporarily dismissed as krama (citizen) due to not being able to pay off debt loans at the Paselatan Traditional Village Credit Institution. Dismissal as a krama of a traditional village in Bali is commonly called a kasepekang indigenous sanction. There is a gap between what should be in the law, both in the regulation and implementation of the law, with the reality that occurred in the Paselatan Traditional Village; There are still traditional Kasepekang sanction which are considered to violate humanism values. This study analyzes: first, the enforcement of the indigenous sanction of kasepekang which are considered to violate the values of legal humanism. Second, the implementation of progressive legal principles in the case of bestowing kasepekang sanction in the Paselatan Traditional Village as a mediator between the legal tensions of the kasepekang indigenous sanction and legal humanism. The research method used is a normative research method. The theory used as an analysis is progressive legal theory. The results of the study concluded that the indigenous sanction of Kasepekang are not in accordance with philosophical, sociological values, and are contrary to the juridical aspects and are contrary to the theoretical aspects, especially the progressive legal theory. Progressive legal principles are applied as an end to the tension between Kasepekang indigenous sanction and legal humanism. Key Words: Tension; kasepekang indigenous sanction; legal humanism AbstrakArena ketegangan antara sanksi adat kasepekang dengan humanisme hukum terjadi di Desa Adat Paselatan, Kabupaten Karangasem, Bali. Satu keluarga yang bertempat tinggal di desa adat tersebut mendapatkan sanksi adat berupa diberhentikan sementara sebagai krama (warga) adat akibat tidak mampu melunasi pinjaman utang di Lembaga Perkreditan Desa Adat Paselatan. Pemberhentian sebagai krama (warga) desa adat di Bali lazim disebut sanksi adat kasepekang. Terdapat kesenjangan antara apa yang seharusnya dalam berhukum, baik dalam pengaturan maupun penerapan hukum, dengan kenyataan yang terjadi di Desa Adat Paselatan; masih ada sanksi adat kasepekang yang dianggap melanggar nilai-nilai humanisme. Penelitian ini menganalisis, pertama, penerapan sanksi adat kasepekang yang dinilai melanggar nilai-nilai humanisme hukum. Kedua, penerapan prinsip-prinsip hukum progresif pada kasus pemberian sanksi kasepekang di Desa Adat Paselatan sebagai penengah ketegangan hukum sanksi adat kasepekang dan humanisme hukum. Metode penelitian yang digunakan adalah metode penelitian normatif. Teori yang digunakan sebagai analisis yakni teori hukum progresif. Hasil penelitian menyimpulkan bahwa sanksi adat kasepekang tidak sesuai dengan nilai filosofis, sosiologis, dan bertentangan dengan aspek yuridis serta bertentangan dengan aspek teoritis khususnya teori hukum progresif. Prinsip-prinsip hukum progresif diterapkan sebagai akhir ketegangan antara sanksi adat kasepekang dengan humanisme hukum. Kata-kata Kunci: Ketegangan; sanksi adat kasepekang; humanisme hukum